2009
DOI: 10.1537/ase.080513
|View full text |Cite
|
Sign up to set email alerts
|

Biological affinities of Okhotsk-culture people with East Siberians and Arctic people based on dental characteristics

Abstract: This paper examines the population affinity of the Okhotsk-culture people who settled along the northeastern coastal areas of the islands of Hokkaido and Sakhalin during the 5th and 11th centuries, on the bases of dental metric and nonmetric features. Based on neighbor-joining analyses of both metric and nonmetric data, the Okhostk people, eastern Siberians, and subarctic American natives were linked more closely to each other than to other East Asian and Pacific samples. In particular, the nonmetric data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
4
12
0
1
Order By: Relevance
“…Possible relationships among the Jomon (and/ or Ainu), prehistoric Europeans, and prehistoric Americans have repeatedly been suggested (Yamaguchi, 1982;Brace et al, 2001;Tokunaga et al, 2001;Jantz and Owsley, 2003;Hanihara and Ishida, 2009) because of lack of craniofacial modernization or gracilization in the Jomon (Suzuki, 1981;Yamaguchi, 1982). This study also supports such an interpretation, although other studies show Jomon affinities with other populations, such as northeastern Asians (Komesu et al, 2008;Matsumura et al, 2009). …”
Section: Jomonsupporting
confidence: 71%
“…Possible relationships among the Jomon (and/ or Ainu), prehistoric Europeans, and prehistoric Americans have repeatedly been suggested (Yamaguchi, 1982;Brace et al, 2001;Tokunaga et al, 2001;Jantz and Owsley, 2003;Hanihara and Ishida, 2009) because of lack of craniofacial modernization or gracilization in the Jomon (Suzuki, 1981;Yamaguchi, 1982). This study also supports such an interpretation, although other studies show Jomon affinities with other populations, such as northeastern Asians (Komesu et al, 2008;Matsumura et al, 2009). …”
Section: Jomonsupporting
confidence: 71%
“…The Jomon are widely thought to have settled the Japanese archipelago c. 15700 to 2350 years BP (Kobayashi, 2008) and ranged geographically from Hokkaido to Okinawa. Morphological studies of dental variation have suggested that the Jomon people were of southern origin (Turner, 1987(Turner, , 1990Hanihara, 1991;Matsumura, 2007;Matsumura et al, 2009). On the other hand, archaeology, genetics, and recent cranial morphology studies suggest that the Jomon people were of northern origin (Nei, 1995;Imamura, 1996;Omoto and Saitou, 1997;Hanihara and Ishida, 2009;Nakashima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly of concern regarding the female Epi-Jomon/Satsumon metric and combined-sex nonmetric datasets. At the same time, it remains possible that sex-related population history and subsistence pattern, as well as differential retention/speciation of phenotypic characteristics between metric and nonmetric dental features, have something to do with such discordance (Hanihara and Ishida, 2005;Hanihara et al, 2008;Hanihara, 2010a;Matsumura et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many dental anthropologists see the Ainu (and the Jomon) as Southeast Asian sundadonts (Turner, 1987(Turner, , 1990(Turner, , 1992aHanihara, 1991;Matsumura, 1995Matsumura, , 2007Matsumura and Hudson, 2005;Manabe et al, 2008;Matsumura et al, 2009). It is often pointed out, moreover, that extensive dental size reduction occurs exclusively in Ainu and their Jomon predecessors, together with the Philippine Negritos in eastern Asia (Brace et al, 1989(Brace et al, , 1991Brace and Hunt, 1990;Hanihara and Ishida, 2005;Matsumura and Hudson, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation